Peningkatan Mutu Kakao Melalui Teknologi Bioproses Pemerasan Pulp (Depulping) Biji Kakao Secara Mekanis - Sumanto Sumanto; Dedi Sholeh Efendi; Bambang Prastowo (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
In general, the classic problems faced by the cocoa farmer are low productivity and quality of cocoa beans as farmers do not perform fermentation due to a longer processing time. Bulk cocoa beans covered with pulp presumably affecting the fermentation time and bean quality. The research objective was to assess a combination of bioprocessing technology and mechanized-depulping to improve the quality of fermented cocoa beans. The study was conducted from July 2011 to July 2012 on cocoa farmer groups in Pacitan Regency, East Java, using engine depulper (500 kg/hour capacity) and manually (20 kg/10 minutes or about 120 kg/hour capacity). The results showed that fermentation time was shorter in squeezed pulp, either using engine depulper or manually. Both the temperature and pH of fermented beans reached its highest point on the fourth day and decreased on day five, from which obtained higher quality beans indicated by clean and bright brown color with better flavour and color as well as lower acidity, astringent, and smell.